Communication : Lithium Ion Concentration Effect in PYR 14 TFSI Ionic Liquid for Li-O 2 Battery Cathodes - Mozhzhukhina, Nataliia (2017)
The oxygen reduction reaction (ORR) has been studied on Au cathodes in O2 saturated PYR14TFSI ionic liquid (IL) electrolyte using cyclic voltammetry, rotating ring disc electrode (RRDE), electrochemical quartz crystal microbalance (EQCM) and differential electrochemical mass spectrometry (DEMS). At different Li+ concentrations in the IL competition of Li+ and PYR14 + for superoxide ion results in dismutation of Li+O2 − and formation of insoluble Li2O2.